A new species of the genus Oxyporus Fabricius (Coleoptera: Staphylinidae: Oxyporinae) in Yunnan Province, China - Li, Guo-Feng; Wang, Chun-Mei; Li, Hua-Feng; Li, Zhu-Jie; Wu, Xing-Xing (Zootaxa, 2019)
A new species of the genus Oxyporus Fabricius, 1775 is described based on specimens collected in Yunnan Province, China, namely Oxyporus (Oxyporus) tuantianius sp. nov. from Xinping County. The number of Oxyporus species worldwide is thus increased to 131. Color images of the habitus and aedeagus of the new species are included. A key to the Oxyporus species of Yunnan Province is provided.